Becoming immersed: Using Virtual Reality technologies in academic libraries to expand outreach and enhance course curricula. Issue 2 (10th November 2021) - Huber, Aleshia; Embree, Jennifer K.; Gay, Amy; Gilman, Neyda V.
Abstract: In the fall of 2018, the Binghamton University Libraries purchased Virtual Reality (VR) headsets and accessories to provide an innovative service on campus and extend its outreach. The availability of the technology through the Libraries' allowed a nursing course to incorporate it into their teaching. The Libraries also hosted monthly VR outreach events and included the technology in a Digital Humanities Research Institute (a four-day intensive workshop). This article explains these uses, describes VR's ability to be adopted into various learning spaces, and discusses the future integration of VR into course curricula. Limitations encountered and potential challenges are also discussed.